Genomic Features of Rickettsia heilongjiangensis Revealed by Intraspecies Comparison and Detailed Comparison With Rickettsia japonica - Kasama, Kentaro; Fujita, Hiromi; Yamamoto, Seigo; Ooka, Tadasuke; Gotoh, Yasuhiro; Ogura, Yoshitoshi; Ando, Shuji; Hayashi, Tetsuya (Frontiers in Microbiology, 2019)
Rickettsia heilongjiangensis is the causative agent of Far-Eastern spotted fever (FESF). In Japan, a human case of FESF was identified in Sendai in Miyagi Prefecture in 2008, and R. heilongjiangensis bacteria were isolated from Haemaphysalis concinna ticks collected in the suspected geographic area of infection. Although the intraspecies genome diversity of Rickettsiae has been poorly investigated, our recent analysis revealed extremely low genomic diversity of R. japonica, the agent of Japanese spotted fever, which is a close relative of R. heilongjiangensis. In this study, to investigate the genomic diversity of R. heilongjiangensis and understand the genetic relationship between Japanese and Chinese strains, we sequenced three strains isolated in Sendai and one strain isolated in Inner Mongolia, China, and performed genomic comparisons between these strains and strain 054, the type strain isolated in Heilongjiang Province, China. Although the three Japanese strains were isolated in 2008, 2009, and 2012, their genome sequences were identical, indicating that H. concinna ticks carrying a single R. heilongjiangensis clone have colonized Sendai, Japan. Among the five R. heilongjiangensis strains, only 81 SNPs and 13 insertion/deletion sites were identified, despite the significant differences in these isolates both geographically and temporally. A significant portion of the 81 SNPs (15/81) were found to be recombinogenic. These results indicate low genomic diversity of R. heilongjiangensis, as observed in R. japonica. We further performed a detailed genomic comparison of R. heilongjiangensis and R. japonica to accurately define conserved and species-specific genes. This analysis revealed that although notable variations were found in the genomic loci encoding RelA/SpoT family proteins and tandem repeats in major surface proteins, there was only a small difference in the gene repertoire between the two species, suggesting that SNPs and small InDels are responsible for the functional or physiological differences between the two species, if present. Through this analysis, several species-specific genomic regions that can serve as ideal PCR targets for distinguishing R. heilongjiangensis and R. japonica were also identified.